EFFECTIVENESS OF THE SELF-HELP HOUSING STIMULUS ASSISTANCE PROGRAM (BSPS) IN JALAN LURUS VILLAGE, SUNGAI PANDAN DISTRICT, HULU SUNGAI UTARA REGENCY - Muhammad Alvie; Yusran Fahmi; Gusti Muhammad Hidayatullah (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2026)
Effectiveness is the level of success of a program to achieve goals quickly. In Straight Road Village, the BSPS program is effective. The problems faced include limited access and information so that many people do not fully understand the mechanism and requirements of the BSPS program, the High Number of Uninhabitable Houses due to economic poverty, Budget Limitations that Hinder the Full Coverage of Aid Recipients. The purpose of this study is to determine the effectiveness of the Self-Help Housing Stimulants Assistance Program in Jalan Straight Village, Sungai Pandan District, North Hulu Sungai Regency and the factors that affect it. The researcher used a qualitative descriptive method by collecting data through observation, interviews and documentation. The data source was taken through informants totaling 15 people purposively . Technical data analysis with data condensation, data display, drawing and verifying conclusions. Test the credibility of the data by extending observations, increasing persistence, triangulation, using reference materials and using memberchecks. The results of the study show that the effectiveness of the Self-Help Housing Stimulant Assistance Program in Jalan Lurus Village, Sungai Pandan District, North Hulu Sungai Regency, North Hulu Sungai Regency, the results are quite effective judging from the indicators: First, the objectives of the program are effective. Second, the requirements for participating in the program are effective for people who participate and have met the requirements. Third, the accuracy target is effective for the community, especially low-income people (MBR). Fourth, socialization is quite effective. Fifth, Participation is still lacking in attendance, besides that inhibiting factors, namely: Limited access and information and limited funds. The driving factors are: clear goals. To increase the effectiveness of the BSPS Program in Jalan Lurus Village, Sungai Pandan District, North Hulu Sungai Regency, DISPERKIM LH and the HSU Regency Government are expected to adjust the assistance funds to the inflation of materials/wages of builders, collaborate with banks for free accounts, increase the local builder budget, build a digital monitoring system, and conduct annual evaluations; to the Head of Jalan Lurus Village and village officials are expected to increase coordination through mutual cooperation so that information is timely, schedule activities on weekends for active participation, so as to overcome low participation due to busyness or lack of information